PENGARUH TERPAAN MEDIA TELEVISI TERHADAP TINGKAT KECEMASAN WALI MURID DI SEKOLAH DASAR NEGERI 80 PEKANBARU TENTANG PEMBERITAAN VAKSIN ANAK - Ulfadilah "; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The government's program for mandatory vaccines for children aged 6-11 years has been intensified from December 2021 to February 2022. The television media also continues to report on the implementation of the impact or effects experienced by users of child vaccines that have the potential to make parents of children anxious about the implementation of children's vaccines in schools. In relation to cultivation theory which states that the more time a person spends watching television, the stronger the tendency for people to equate social reality. In this study, respondents who often watched news on children's vaccines tended to feel anxious. The purpose of this study was to determine whether there was an effect of television media exposure about the news of children's vaccines on the anxiety level of the parents of 80 Pekanbaru public elementary school students. The method used in this study is a quantitative method with statistical analysis. Researchers collect data using questionnaires and documentation. The location of this research is at the 80 Pekanbaru State Elementary School with a total sample of 100 respondents using a sampling technique Purposive Sampling. Sample whose population is unknown because the population of respondents who watch news on children's vaccines on television is not known for certain. To determine the relationship between variables, researchers used simple linear regression analysis. While the questionnaire for processing the test data was carried out using the Statistical Product and Service Solutions (SPSS) Windows version 24. The results of this study are based on simple linear regression, the regression coefficient obtained is Y = 11.371 + 0.117 X with a significance level of 0.000 and less than = 0.05. While the results of the determination test obtained 38.6%. It means that there is a small or weak influence from television media exposure about news of children's vaccines on the anxiety level of the guardians of the 80 Pekanbaru State Elementary School students. While the remaining 61.4% is influenced by factors outside this study.